Enhancing EFL Writing Skills Through Technology: An Evaluation of EPSS Multimedia Lab and CleverCookie - Torrado Cespón, Milagros; Díaz Lage, José María (Foro De Educacion, 2026)
The widespread use of the Internet has significantly influenced written language, particularly in online communication. This study explores the impact of digital writing on English as a Foreign Language (EFL) learners, focusing on two online tools designed for Spanish-speaking users: EPSS Multimedia Lab and CleverCookie. The research examines how these tools contribute to improving students’ grammatical accuracy and phonetic awareness in online environments. A mixed-methods approach was employed. with 145 university students divided into two groups: G1 (n = 76), specialising in English Studies, assessed EPSS Multimedia Lab, while G2 (n=69), comprising pre-service primary school teachers, evaluated CleverCookie. Data were collected through qualitative surveys, where participants provided feedback on the strengths and limitations of each tool. Results indicate that EPSS Multimedia Lab was particularly beneficial for phonetic training, with students appreciating its structured exercises and accessibility. However, they also identified issues such as limited accent variety and transcription errors. CleverCookie was praised for its clarity, simplicity, and bilingual support, but students expressed the need for more interactive content and a broader range of topics. The findings underscore the necessity of continuous improvements in digital language-learning tools. Future developments will focus on expanding content, increasing interactivity, and integrating adaptive learning features to better cater to student needs.
La mejora de las habilidades de escritura en EFL a través de la tecnología: Una evaluación de EPSS Multimedia Lab y CleverCookie
El uso generalizado de Internet ha influido significativamente en la escritura, especialmente en la comunicación en línea. Este estudio explora el impacto de la escritura digital en los estudiantes de inglés como lengua extranjera (ILE), centrándose en dos herramientas diseñadas para hablantes de español: EPSS Multimedia Lab y CleverCookie. La investigación analiza cómo estas herramientas contribuyen a mejorar la precisión gramatical y la conciencia fonética de los estudiantes en entornos digitales. Se empleó un enfoque de métodos mixtos, con 145 estudiantes universitarios divididos en dos grupos: G1 (n= 76), compuesto por estudiantes de Estudios Ingleses, evaluó EPSS Multimedia Lab, mientras que G2 (n=69), formado por futuros maestros de primaria, evaluó CleverCookie. Se recopilaron datos a través de encuestas cualitativas, donde los participantes proporcionaron comentarios sobre las fortalezas y limitaciones de cada herramienta. Los resultados indican que EPSS Multimedia Lab fue especialmente beneficiosa para el entrenamiento fonético, destacando sus ejercicios estructurados y accesibilidad. No obstante, los estudiantes identificaron limitaciones como la variedad de acentos y errores de transcripción. CleverCookie fue valorada por su claridad, simplicidad y soporte bilingüe, aunque se destacó la necesidad de mayor interactividad y una ampliación de los temas abordados. Los hallazgos subrayan la necesidad de mejoras continuas en las herramientas digitales de aprendizaje de idiomas. Futuras actualizaciones se centrarán en expandir el contenido, aumentar la interactividad e integrar características de aprendizaje adaptativo para satisfacer mejor las necesidades de los estudiantes.
Keywords: digital writing in EFL; online language learning tools; Technology-Enhanced Language Learning (TELL); EFL learners; escritura digital; herramientas de aprendizaje en línea; aprendizaje de lenguas mediado por tecnología (TELL); aprendices de ILE